Nanoencapsulated aroma finishing on fabric by sol-gel process - W. N. W., Ismail (AIP Publishing, 2021)
An essential component of the medium that influences the effects and duration of aroma release is sustained- release materials. Encapsulation of aromas into nanomaterials is an innovative and efficient method of application. Nanocapsules enclose and shield their core materials against environmental reactions, which are then intentionally released at a specified time. The possibility of determining performance in such an accurate manner is the reason for the many industrial applications. Numerous nanocapsule systems, including natural, semisynthetic, and synthetic materials, demonstrate how developed this field is. A variety of methods for the manufacture of aromatic nanocapsules have been utilized. The sol-gel process is among the most widely used technique. Both of the colloid particles and the emulsion as templates are coated by controlled surface precipitation of nanoparticles in a typical sol-gel method. Template particles that are utilized are removed via selective dissolution in a suitable solvent or by calcination at an elevated air temperature, resulting in the desired nanocapsules left behind. The obtained nanocapsules can load aroma through physical adsorption and maintain exceptional morphology. Finally, the aroma of the nanocapsules is used to finish the fabric aromatically. This review briefly describes the preparation of aroma nanocapsules using the sol-gel method and the applications of the nanocapsules in fabric finishing.